1994
DOI: 10.1002/anie.199407311
|View full text |Cite
|
Sign up to set email alerts
|

Metallocorroles with Formally Tetravalent Iron

Abstract: Dtw'ilctrtecl to Piofcrc.or Eimt Otto F i~t h e r 017 the> ol c ci\ioi? of h r~ 75th birt~7da1The coordination chemistry of metals in unusual oxidation states is a fascinating aspect of research in the field ofmetalloporphyrins. Of particular significance in this respect are oxoiron porphyrins containing tetravalent iron, since complexes of this sort occur as reactive intermediates in numerous biological and biomimetic oxidation processes."] Iron(iv) porphyrins, in which the metal is not present as part of a [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
208
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(236 citation statements)
references
References 48 publications
26
208
1
1
Order By: Relevance
“…[4,18] We have now found that it is possible to use one common starting point for the synthesis of many iron complexes of 4, and controlling the oxidation state of iron and its ligands by either the adopted workup procedure or the interconversions shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,18] We have now found that it is possible to use one common starting point for the synthesis of many iron complexes of 4, and controlling the oxidation state of iron and its ligands by either the adopted workup procedure or the interconversions shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…[2] The somewhat contracted coordination core of corroles and the fact that they act as trianionic ligands leads to what is the most outstanding feature of corroles relative to porphyrins and other organic ligands, that is, the stabilization of metal ions in high oxidation states. The most relevant examples from the first-row transition metals include complexes of electron-rich corroles with chromium(v), [3] iron(iv), [4] cobalt(iv), and even cobalt(v). [5] This phenomenon is especially surprising, since the Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…1) plays a special role, because it was one of the first examples reported in the literature [9] and, more recently, because some of its electronic and chemical properties hold particular value for researchers [10]. For example, corrole is able to coordinate a wide range of metal ions, stabilizing higher oxidation states than do the related porphyrins [11][12][13]. Furthermore, corrole is usually able to maintain a planar conformation even if fully substituted at the peripheral positions [14].…”
Section: Introductionmentioning
confidence: 97%
“…[11] In many cases,u nusually high oxidation states that are unlikely to be stabilized by other ligand environments are found to be stable inside the corrolato cavity.T he trianionic nature of the corrolato ligand is certainly helpful for this purpose.Some of the higher oxidation states of metals that have been stabilized in corrolato environments include Cu ,and Cr VI . [12] We have recently presented unambiguous experimental and theoretical evidence for the existence of Ag II and Ag III within the same corrolato framework.…”
Section: Introductionmentioning
confidence: 99%